Aksent va dialektning sinxron tarjimada roli - Turg’unova Irodaxon Xayrulla qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article analyzes the impact of accents and dialects on the simultaneous interpretation process, methods to overcome them, and effective strategies for interpreters.